A hard carbon negative electrode material and preparation method thereof and sodium ion battery
Through the mixing and granulation process of asphalt slurry and hardcock material, a core-shell structure is formed, which solves the problems of low asphalt coating rate and excessive dust in the prior art, and significantly improves the electrochemical performance and cycle stability of hardcock negative electrode materials.
Patent Information
- Application Number
- CN202510273778.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing asphalt-covered hard charcoal has problems with low cladding rate and excessive dust, resulting in high production costs and poor material circulation stability.
The asphalt slurry and hard carbon material are used for mixing and granulation processes to form a core-shell structure, repair the surface defects of the hard carbon and reduce the specific surface area.
The first Coulomb efficiency and cycle stability of hard carbon anode material are improved, production costs are reduced, and the electrochemical properties of the material are enhanced.
Smart Images

Figure CN119750549A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have attracted much attention in energy storage applications due to their similar energy storage mechanism to lithium-ion batteries, abundant raw materials, and high safety performance.
[0003] As one of the core components of sodium-ion batteries, the hard carbon anode has structural characteristics such as the degree of graphitization, degree of defects, and pore structure that affect the battery's first coulombic efficiency, rate performance, and cycle durability. Hard carbon is a carbon material that is difficult to graphitize even at high temperatures above 2500°C. As a negative electrode material for sodium-ion batteries, hard carbon can achieve relatively high gram capacity and first efficiency. In addition, hard carbon anodes are safer than graphite anodes and have better cycle performance and rate performance. However, hard carbon has the disadvantage of a large specific surface area, especially hard carbon obtained after the block is crushed, which has a larger specific surface area and more active sites on the particle surface, resulting in an increase in side reactions during the actual application of high current charging and discharging, and the phenomenon of sodium precipitation is prone to occur, thereby reducing the safety performance and cycle stability of sodium-ion batteries. Asphalt coating can effectively cover the active sites on the surface of hard carbon and reduce the specific surface area, thereby improving the electrochemical performance of the material. However, the existing asphalt-coated hard carbon has the problems of low coating rate and excessive dust during coating, and waste is generated during the coating process, which significantly increases the production cost.
[0004] Therefore, how to solve the problems of low coating rate and excessive dust during asphalt coating of existing asphalt-coated hard carbon, so as to effectively reduce waste and reduce production costs, and further improve the first rate and cycle stability of hard carbon negative electrode materials, is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a hard carbon negative electrode material and a preparation method thereof and a sodium ion battery. The present invention uses asphalt slurry and hard carbon material to carry out kneading and granulation processes, which can not only solve the problems of low coating rate of asphalt-coated hard carbon and excessive dust during asphalt coating, but also can repair the surface defects of the hard carbon material in one step. During the granulation process, a layer of amorphous carbon protective layer converted from asphalt slurry is modified on the surface of the hard carbon material, thereby constructing a core-shell structure, which can reduce the interface resistance between the hard carbon negative electrode material and the electrolyte, so that the hard carbon material retains its advantages of high capacity and low potential, and its outer shell has good electrolyte compatibility, which can effectively inhibit the adverse effects caused by the solvation effect, and significantly improve the first coulomb efficiency and cycle stability of the hard carbon negative electrode material. This process has high efficiency, good stability and low cost during industrial scale-up.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a hard carbon negative electrode material, the preparation method comprising the following steps: (1) mixing the hard carbon material and the asphalt slurry, and kneading them to obtain a kneaded material; (2) The kneaded material is melt-granulated and then sintered to obtain the hard carbon negative electrode material.
[0007] The present invention uses asphalt slurry and hard carbon material to perform kneading and granulation processes, which can not only solve the problems of low coating rate and excessive dust during asphalt coating of hard carbon, but also can repair the surface defects of hard carbon material in one step. During the granulation process, a layer of amorphous carbon protective layer converted from asphalt slurry is modified on the surface of the hard carbon material, thereby constructing a core-shell structure, which can reduce the interface resistance between the hard carbon negative electrode material and the electrolyte, so that the hard carbon material retains its advantages of high capacity and low potential, and its shell has good electrolyte compatibility, which can effectively inhibit the adverse effects caused by the solvation effect, and significantly improve the first coulomb efficiency and cycle stability of the hard carbon negative electrode material. The liquid phase coating process is highly efficient, stable, and low-cost during industrial amplification.
[0008] The method of liquid phase coating provided by the present invention is conducive to the synthesis of core-shell powders with high purity, narrow particle size distribution, controllable component morphology, and dense and uniform shell. Secondly, in the liquid phase, the substance can be evenly dispersed in the state of molecules or ions. Since the thermal motion of liquid molecules is relatively active, it can promote better mutual penetration and diffusion between different components. In contrast, solid phase mixing mainly relies on mechanical force to make particles contact and mix with each other, and it is difficult to achieve uniform dispersion at the molecular level. In particular, the liquid phase environment is conducive to the conduction of chemical reactions. The distance between molecules in the liquid is closer, and there are more opportunities for mutual collision, so as to accelerate the rate of chemical reactions. At the same time, liquid phase kneading can improve the interface bonding between different components, and the interface of different substances can form a closer contact, reduce interface defects, and improve interface bonding strength.
[0009] Preferably, the hard carbon material in step (1) is a coal-based hard carbon material.
[0010] Preferably, the raw material for preparing the coal-based hard carbon material includes any one or a combination of at least two of long flame coal, anthracite, bituminous coal, lignite, lean coal, lean coal, coking coal, gas coal or fat coal, preferably long flame coal.
[0011] Preferably, the step of preparing the asphalt slurry in step (1) comprises: The solid asphalt and the solvent are mixed to obtain the asphalt slurry.
[0012] Preferably, the solid asphalt is petroleum asphalt.
[0013] Preferably, the ratio between the solid asphalt and the solvent, in parts by weight, comprises: The solid asphalt is 6-40 parts, for example, it can be 6 parts, 10 parts, 20 parts, 30 parts or 40 parts, etc., and the solvent is 10-50 parts, for example, it can be 10 parts, 20 parts, 30 parts, 40 parts or 50 parts, etc.
[0014] Preferably, during the mixing process of the solid asphalt and the solvent, an auxiliary material is also added, and the auxiliary material includes any one of ethanol, toluene, acetone, petroleum ether, pyridine or tetrahydrofuran, or a combination of at least two of them.
[0015] In the present invention, the introduction of auxiliary materials as mixing aids helps to make the asphalt and the solvent mix more fully, thereby improving the mixing degree of the asphalt slurry.
[0016] Preferably, the mass ratio of the solid asphalt to the auxiliary material is 1:(2-10), for example, it can be 1:2, 1:4, 1:6, 1:8 or 1:10, etc.
[0017] In the present invention, if the mass ratio of solid asphalt and auxiliary material is too large, that is, the amount of auxiliary material is too small, the mixing of asphalt and solvent is insufficient, and solid-liquid separation is likely to occur; if the mass ratio of solid asphalt and auxiliary material is too small, that is, the amount of auxiliary material is too much, it will cause waste of auxiliary material, and at the same time, the auxiliary material will affect the surface structure of the coated hard carbon material in the subsequent process, resulting in a reduction in its electrochemical primary effect.
[0018] Preferably, the ratio between the hard carbon material and the asphalt slurry in step (1) comprises, in parts by weight: The hard carbon material is 450-1200 parts, for example, it can be 450 parts, 500 parts, 750 parts, 1000 parts or 1200 parts, etc., and the asphalt slurry is 8-50 parts, for example, it can be 8 parts, 10 parts, 20 parts, 30 parts, 40 parts or 50 parts, etc.
[0019] In the present invention, the hard carbon material and asphalt slurry in a suitable ratio help to form a more uniform core-shell structure, which is beneficial to the improvement of electrochemical performance.
[0020] Preferably, the kneading temperature of the kneading treatment in step (1) is 50-300°C, for example, it can be 50°C, 100°C, 150°C, 200°C, 250°C or 300°C, etc., preferably 200-300°C.
[0021] In the present invention, if the kneading temperature of the kneading treatment is too low, the viscosity of the asphalt slurry increases, the machine operating load is large, the difficulty of kneading and stirring evenly increases, the density of the paste deteriorates, and the plasticity also deteriorates; if the kneading temperature of the kneading treatment is too high, the light components of the heated part of the asphalt gradually decompose and volatilize, the oxidation effect of the hydrocarbons in the asphalt also becomes stronger, the plasticity deteriorates, and the yield of the molding is affected.
[0022] Preferably, the kneading process in step (1) is accompanied by stirring, the stirring linear speed is 2.2-10 m / s, for example, 2.2 m / s, 4 m / s, 6 m / s, 8 m / s or 10 m / s, etc., and the stirring time is 20-80 min, for example, 20 min, 40 min, 60 min or 80 min, etc.
[0023] Preferably, the melt granulation process in step (2) is accompanied by stirring, the stirring linear speed is 10-42 m / s, for example, 10 m / s, 20 m / s, 30 m / s, 40 m / s or 42 m / s, etc., and the stirring time is 45-135 min, for example, 45 min, 60 min, 75 min, 100 min or 135 min, etc.
[0024] Preferably, the temperature of the melt granulation in step (2) is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C.
[0025] In the present invention, if the temperature of melt granulation is too low, the fluidity of the material is too poor, which may easily cause particle deformation and result in more holes in the finished product; if the temperature of melt granulation is too high, the material is overheated and decomposed rapidly, resulting in a decrease in material performance.
[0026] Preferably, the sintering process in step (2) is carried out in an inert atmosphere.
[0027] The present invention does not limit the gas in the inert atmosphere, and illustratively, it may be nitrogen, argon or helium.
[0028] Preferably, the sintering temperature in step (2) is 1100-1600°C, for example, it can be 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, and the holding time is 1-10h, for example, it can be 1h, 3h, 5h, 7h or 9h.
[0029] Preferably, the heating rate of the sintering in step (2) is 1-10°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 7°C / min or 9°C / min, and preferably 2-8°C / min.
[0030] Preferably, the preparation method comprises the following steps: (a) The solid asphalt is crushed to a particle size D50 of 0.5-2 μm (for example, 0.5 μm, 1 μm, 1.5 μm or 2 μm, etc.), and then the crushed solid asphalt, auxiliary materials and water are mixed in a high-speed shearing machine for 15-90 min (for example, 15 min, 30 min, 50 min, 75 min or 90 min, etc.) to obtain an asphalt slurry.
[0031] Among them, the stirring line speed of the high-speed shearing machine is 5-26m / s, and the ratio between the solid asphalt and water is calculated by weight, including: 6-40 parts of solid asphalt and 10-50 parts of water; the mass ratio of the solid asphalt and auxiliary materials is 1:(2-10).
[0032] (b) placing a coal-based hard carbon material with a particle size D50 of 4-30 μm (eg, 4 μm, 10 μm, 20 μm, or 30 μm, etc.) in a kneader, and then adding the asphalt slurry for kneading to obtain a kneaded material.
[0033] Among them, the ratio between the hard carbon material and the asphalt slurry is calculated by weight, including: 450-1200 parts of hard carbon material and 8-50 parts of asphalt slurry; the kneading temperature of the kneading treatment is 50-300°C; the kneading process is accompanied by stirring, the stirring linear speed is 2.2-10m / s, and the stirring time is 20-80min.
[0034] (c) placing the kneaded material in a mechanical fusion machine and performing melt granulation at a temperature of 300-500° C., so that the asphalt is coated on the surface of the coal-based hard carbon material to form spherical particles.
[0035] The melt granulation process is accompanied by stirring, the stirring line speed is 10-42 m / s, and the stirring time is 45-135 min.
[0036] (d) In an inert atmosphere, the temperature is raised to 1100-1600° C. at a heating rate of 1-10° C. / min, the spherical particles are sintered for 1-10 h, and then cooled to room temperature to obtain the hard carbon negative electrode material.
[0037] In a second aspect, the present invention provides a hard carbon negative electrode material, which is prepared by the preparation method described in the first aspect.
[0038] In a third aspect, the present invention provides a sodium ion battery, wherein the negative electrode plate of the sodium ion battery comprises the hard carbon negative electrode material as described in the second aspect.
[0039] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes asphalt slurry and hard carbon material for kneading and granulation processes, which can not only solve the problems of low coating rate and excessive dust during asphalt coating of hard carbon, but also can repair the surface defects of hard carbon material in one step. During the granulation process, a layer of amorphous carbon protective layer converted from asphalt slurry is modified on the surface of the hard carbon material, thereby constructing a core-shell structure, which can reduce the interface resistance between the hard carbon negative electrode material and the electrolyte, so that the hard carbon material retains its advantages of high capacity and low potential, while its outer shell has good electrolyte compatibility, which can effectively inhibit the adverse effects caused by the solvation effect, and significantly improve the first coulombic efficiency and cycle stability of the hard carbon negative electrode material.
[0041] (2) The process is highly efficient, stable and low-cost during industrial scale-up. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a process flow chart provided for Example 1 of the present invention.
[0043] Figure 2 This is a transmission electron microscope image of the hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0045] It should be noted that the room temperature below refers to 25°C.
[0046] Example 1 This embodiment provides a method for preparing a hard carbon negative electrode material, and its process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps: (1) The petroleum asphalt is crushed to a particle size D50 of 1 μm, and then the crushed petroleum asphalt, auxiliary materials and water are mixed in a high-speed shearing machine for 45 minutes to obtain an asphalt slurry.
[0047] The stirring line speed of the high-speed shearing machine is 12 m / s, and the ratio between the petroleum asphalt and water is calculated by weight, including: 20 parts of petroleum asphalt and 30 parts of water; the mass ratio of the petroleum asphalt to the auxiliary materials is 1:3.
[0048] (2) Using long flame coal as raw material, a coal-based hard carbon material with a particle size D50 of 15 μm is prepared by air flow pulverization method, and then placed in a kneader, and then the asphalt slurry is added for kneading to obtain a kneaded material.
[0049] Among them, the ratio between the coal-based hard carbon material and the asphalt slurry is calculated by weight, including: 850 parts of hard carbon material and 25 parts of asphalt slurry; the kneading temperature of the kneading treatment is 200°C; the kneading process is accompanied by stirring, the stirring linear speed is 6m / s, and the stirring time is 50min.
[0050] (3) placing the kneaded material in a mechanical fusion machine and performing melt granulation at a temperature of 400° C., so that the asphalt is coated on the surface of the coal-based hard carbon material to form spherical particles.
[0051] The melt granulation process is accompanied by stirring, the stirring line speed is 26 m / s, and the stirring time is 90 min.
[0052] (4) In a nitrogen atmosphere, the temperature is raised to 1350° C. at a heating rate of 5° C. / min, the spherical particles are sintered for 5 h, and then cooled to room temperature to obtain the hard carbon negative electrode material.
[0053] Figure 2 The transmission electron microscope image of the hard carbon negative electrode material prepared in this embodiment is shown. It can be seen from the image that there is an ordered coating layer structure on the surface of the hard carbon negative electrode material, and the interior is still a typical hard carbon disordered structure.
[0054] Example 2 This embodiment provides a method for preparing a hard carbon negative electrode material, the preparation method comprising the following steps: (1) The petroleum asphalt is crushed to a particle size D50 of 0.5 μm, and then the crushed petroleum asphalt, auxiliary materials and water are mixed in a high-speed shearing machine for 15 minutes to obtain an asphalt slurry.
[0055] The stirring line speed of the high-speed shearing machine is 25 m / s, and the ratio between the petroleum asphalt and water is calculated by weight, including: 10 parts of petroleum asphalt and 50 parts of water; the mass ratio of the petroleum asphalt to the auxiliary materials is 1:5.
[0056] (2) Using long flame coal as raw material, a coal-based hard carbon material with a particle size D50 of 5 μm is prepared by air flow pulverization method, and then placed in a kneader, and then the asphalt slurry is added for kneading to obtain a kneaded material.
[0057] Among them, the ratio between the coal-based hard carbon material and the asphalt slurry is calculated by weight, including: 500 parts of hard carbon material and 50 parts of asphalt slurry; the kneading temperature of the kneading treatment is 100°C; the kneading process is accompanied by stirring, the stirring linear speed is 2.5m / s, and the stirring time is 80min.
[0058] (3) The kneaded material is placed in a mechanical fusion machine and melt-granulated at a temperature of 300° C., so that the asphalt is coated on the surface of the coal-based hard carbon material to form spherical particles.
[0059] The melt granulation process is accompanied by stirring, the stirring line speed is 10 m / s, and the stirring time is 135 min.
[0060] (4) In a nitrogen atmosphere, the temperature is raised to 1100° C. at a heating rate of 5° C. / min, the spherical particles are sintered for 10 h, and then cooled to room temperature to obtain the hard carbon negative electrode material.
[0061] Example 3 This embodiment provides a method for preparing a hard carbon negative electrode material, the preparation method comprising the following steps: (1) The petroleum asphalt is crushed to a particle size D50 of 2 μm, and then the crushed petroleum asphalt, auxiliary materials and water are mixed in a high-speed shearing machine for 90 minutes to obtain an asphalt slurry.
[0062] The stirring line speed of the high-speed shearing machine is 5 m / s, and the ratio between the petroleum asphalt and water is calculated by weight, including: 40 parts of petroleum asphalt and 10 parts of water; the mass ratio of the petroleum asphalt to the auxiliary material is 1:9.
[0063] (2) Using long flame coal as raw material, a coal-based hard carbon material with a particle size D50 of 30 μm is prepared by air flow pulverization method, and then placed in a kneader, and then the asphalt slurry is added for kneading to obtain a kneaded material.
[0064] Among them, the ratio between the coal-based hard carbon material and the asphalt slurry is calculated by weight, including: 1200 parts of hard carbon material and 10 parts of asphalt slurry; the kneading temperature of the kneading treatment is 300°C; the kneading process is accompanied by stirring, the stirring linear speed is 10m / s, and the stirring time is 20min.
[0065] (3) placing the kneaded material in a mechanical fusion machine and performing melt granulation at a temperature of 500° C., so that the asphalt is coated on the surface of the coal-based hard carbon material to form spherical particles.
[0066] The melt granulation process is accompanied by stirring, the stirring line speed is 42 m / s, and the stirring time is 45 min.
[0067] (4) In a nitrogen atmosphere, the temperature is raised to 1600° C. at a heating rate of 5° C. / min, the spherical particles are sintered for 1 hour, and then cooled to room temperature to obtain the hard carbon negative electrode material.
[0068] Example 4 The difference between this embodiment and embodiment 1 is that no auxiliary materials are added to the asphalt slurry in step (1).
[0069] The rest of the preparation methods and parameters were the same as those in Example 1.
[0070] Example 5 The difference between this embodiment and embodiment 1 is that the mass ratio of the petroleum asphalt to the auxiliary material in step (1) is 1:12.
[0071] The rest of the preparation methods and parameters were the same as those in Example 1.
[0072] Example 6 The difference between this embodiment and embodiment 1 is that the number of portions of asphalt slurry in step (2) is 5 portions.
[0073] The rest of the preparation methods and parameters were the same as those in Example 1.
[0074] Example 7 The difference between this embodiment and embodiment 1 is that the number of portions of asphalt slurry in step (2) is 60 portions.
[0075] The rest of the preparation methods and parameters were the same as those in Example 1.
[0076] Example 8 The difference between this embodiment and embodiment 1 is that the kneading temperature of the kneading treatment in step (2) is 40°C.
[0077] The rest of the preparation methods and parameters were the same as those in Example 1.
[0078] Example 9 The difference between this embodiment and embodiment 1 is that the kneading temperature of the kneading treatment in step (2) is 400°C.
[0079] The rest of the preparation methods and parameters were the same as those in Example 1.
[0080] Example 10 The difference between this embodiment and embodiment 1 is that the temperature of the melt granulation in step (3) is 200°C.
[0081] The rest of the preparation methods and parameters were the same as those in Example 1.
[0082] Embodiment 11 The difference between this embodiment and embodiment 1 is that the temperature of the melt granulation in step (3) is 600°C.
[0083] The rest of the preparation methods and parameters were the same as those in Example 1.
[0084] Comparative Example 1 The difference between this comparative example and Example 1 is that step (1) is not performed, but the petroleum asphalt solid powder and the coal-based hard carbon material are directly mixed and kneaded.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Performance Testing The hard carbon negative electrode materials prepared in the above embodiments and comparative examples are assembled to obtain sodium ion button batteries, and the specific steps include: (a) The hard carbon negative electrode material is made into a negative electrode sheet, and the preparation method includes: mixing the hard carbon negative electrode material, Super P, CMC and SBR in a mass ratio of 91:2:2:5 to prepare a slurry, then scraping the slurry on a carbon-coated copper foil, and then transferring it to a 65° C. forced air drying oven until the sheet is dry (about 1.5 hours), and then transferring it to a vacuum drying oven for drying for 12 hours to obtain a negative electrode sheet.
[0087] (b) The negative electrode sheet, the positive electrode sheet (metal sodium sheet), the GF / D glass fiber separator and the 1 mol / L NaClO4 electrolyte were assembled to obtain a sodium ion button battery.
[0088] The above sodium-ion batteries were subjected to initial efficiency tests and cycle stability tests.
[0089] First test: voltage range 0-2V, current density 30mA g -1 Carry out charge and discharge test under the conditions to obtain the first effect; Cycle test: voltage range 0-2V, 0.5C charge / 0.2C discharge, repeat the charge and discharge test, after 200 cycles, observe the capacity retention value, and divide this value by the initial capacity value to get the capacity retention rate.
[0090] The test results are shown in Table 1.
[0091] Table 1
[0092] analyze: As can be seen from the above table, the present invention utilizes asphalt slurry and hard carbon material for kneading and granulation processes, which can not only solve the problems of low coating rate of asphalt-coated hard carbon and excessive dust during asphalt coating, but also can repair the surface defects of the hard carbon material in one step. During the granulation process, a layer of amorphous carbon protective layer converted from asphalt slurry is modified on the surface of the hard carbon material, thereby constructing a core-shell structure, which can reduce the interface resistance between the hard carbon negative electrode material and the electrolyte, so that the hard carbon material retains its advantages of high capacity and low potential, while its outer shell has good electrolyte compatibility, which can effectively inhibit the adverse effects caused by the solvation effect, and significantly improve the first coulombic efficiency and cycle stability of the hard carbon negative electrode material.
[0093] It can be seen from Example 1 and Examples 4-5 that if no auxiliary materials are added to the asphalt slurry, the powder will not be able to fully fuse with the solvent, resulting in solid-liquid separation, and the solvent ions will not be able to combine the powder with the material, resulting in the inability to repair the surface defects of the material; if the amount of auxiliary materials added to the asphalt slurry is too much, it will cause a waste of auxiliary materials. At the same time, the auxiliary materials will affect the surface structure of the coated hard carbon material in the subsequent process, resulting in a reduction in its electrochemical initial efficiency.
[0094] It can be seen from Example 1 and Examples 6-7 that if the amount of asphalt slurry in step (2) is too small, a part of the material will not be able to be evenly mixed with the slurry, resulting in the inability of some of the material to construct a core-shell structure; if the amount of asphalt slurry in step (2) is too large, the coating layer will be too thick, which will directly affect the performance of the hard carbon product, especially its reversible capacity and first-effect properties.
[0095] It can be seen from Example 1 and Examples 8-9 that if the kneading temperature of the kneading treatment in step (2) is too low, the auxiliary materials used cannot be completely precipitated, resulting in the incorporation of impurity elements, affecting the primary properties of the hard carbon product; if the kneading temperature of the kneading treatment in step (2) is too high, some components of the asphalt will be oxidized in the air environment, reducing the rheological properties of the asphalt, resulting in the coating layer not being able to achieve a uniform coating effect.
[0096] It can be seen from Example 1 and Examples 10-11 that if the temperature of the melt granulation in step (3) is too low, the surface structure will be deformed and a stable core-shell structure cannot be formed; if the temperature of the melt granulation in step (3) is too high, the temperature is too high and the solidification rate of the asphalt in the asphalt slurry is too fast, causing the asphalt to solidify before it is evenly distributed on the hard carbon surface.
[0097] It can be seen from Example 1 and Comparative Example 1 that if step (1) is not performed and the petroleum asphalt solid powder and the coal-based hard carbon material are directly mixed and kneaded, the powder and the material cannot form an amorphous carbon protective layer.
[0098] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing the hard carbon material and the asphalt slurry, and kneading them to obtain a kneaded material; (2) The kneaded material is melt-granulated and then sintered to obtain the hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The hard carbon material in step (1) is a coal-based hard carbon material; And / or, the step of preparing the asphalt slurry in step (1) comprises: Mixing solid asphalt and solvent to obtain the asphalt slurry; The solid asphalt is petroleum asphalt; The ratio between the solid asphalt and the solvent is calculated by weight and includes: 6-40 parts of solid asphalt and 10-50 parts of solvent.
3. The preparation method according to claim 2, characterized in that: During the mixing of the solid asphalt and the solvent, an auxiliary material is also added, and the auxiliary material includes any one of ethanol, toluene, acetone, petroleum ether, pyridine or tetrahydrofuran, or a combination of at least two thereof; The mass ratio of the solid asphalt to the auxiliary material is 1:(2-10).
4. The preparation method according to claim 1, characterized in that: The ratio of the hard carbon material and the asphalt slurry in step (1) is calculated by weight and includes: 450-1200 parts of hard carbon material and 8-50 parts of asphalt slurry.
5. The preparation method according to claim 1, characterized in that: The kneading temperature of the kneading treatment in step (1) is 50-300°C, preferably 200-300°C; And / or, the kneading process in step (1) is accompanied by stirring, the stirring linear speed is 2.2-10 m / s, and the stirring time is 20-80 min.
6. The preparation method according to claim 1, characterized in that: The melt granulation process in step (2) is accompanied by stirring, the stirring line speed is 10-42 m / s, and the stirring time is 45-135 min; And / or, the temperature of the melt granulation in step (2) is 300-500°C.
7. The preparation method according to claim 1, characterized in that: The sintering process in step (2) is carried out in an inert atmosphere; And / or, the sintering temperature in step (2) is 1100-1600° C. and the holding time is 1-10 h; And / or, the heating rate of the sintering in step (2) is 1-10°C / min, preferably 2-8°C / min.
8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (a) crushing the solid asphalt to a particle size D50 of 0.5-2 μm, and then mixing the crushed solid asphalt, auxiliary materials and water in a high-speed shearing machine for 15-90 minutes to obtain an asphalt slurry; The stirring line speed of the high-speed shearing machine is 5-26 m / s, and the ratio between the solid asphalt and water is calculated by weight, including: 6-40 parts of solid asphalt and 10-50 parts of water; the mass ratio of the solid asphalt to the auxiliary material is 1: (2-10); (b) placing a coal-based hard carbon material with a particle size D50 of 4-30 μm in a kneader, and then adding the asphalt slurry to perform kneading treatment to obtain a kneaded material; The ratio of the hard carbon material to the asphalt slurry is calculated by weight, including: 450-1200 parts of the hard carbon material and 8-50 parts of the asphalt slurry; the kneading temperature of the kneading treatment is 50-300°C; the kneading process is accompanied by stirring, the stirring line speed is 2.2-10m / s, and the stirring time is 20-80min; (c) placing the kneaded material in a mechanical fusion machine and performing melt granulation at a temperature of 300-500° C., so that the asphalt is coated on the surface of the coal-based hard carbon material to form spherical particles; The melt granulation process is accompanied by stirring, the stirring line speed is 10-42 m / s, and the stirring time is 45-135 min; (d) In an inert atmosphere, the temperature is raised to 1100-1600° C. at a heating rate of 1-10° C. / min, the spherical particles are sintered for 1-10 h, and then cooled to room temperature to obtain the hard carbon negative electrode material.
9. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The negative electrode plate of the sodium ion battery includes the hard carbon negative electrode material as claimed in claim 9.
Citation Information
Patent Citations
Sodium-ion battery core-shell structure bagasse hard carbon-based negative electrode material and preparation method thereof
CN116332152A
Coal-based hard carbon negative electrode material and preparation method and application thereof
CN118598120A
High-capacity resin / asphalt-based hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN118993024A
Oxidized crosslinked asphalt coated resin hard carbon negative electrode material and preparation method thereof
CN119581533A
Graphite negative electrode material for high-performance lithium ion battery and preparation method therefor
WO2021189836A1
Cited By
Controllable construction method for carbon layer structure on hard carbon surface and application of controllable construction method
CN120463182A